Lacan with the philosophers - Ronen, Ruth (University of Toronto Press, 2018)
Lacan with the Philosophers creates a dialogue between the oeuvre of psychoanalyst Jacques Lacan and philosophy. Major philosophical figures to which Lacan vastly referred are examined around key concepts fundamental to philosophy - being, truth, knowledge, the good, the subject.